The Endogenous and Cell Cycle-dependent Phosphorylation of tau Protein in Living Cells: Implications for Alzheimer’s Disease - Illenberger, Susanne (The American Society for Cell Biology, 1998)
In Alzheimer’s disease the neuronal microtubule-associated protein tau becomes highly phosphorylated, loses its binding properties, and aggregates into paired helical filaments. There is increasing evidence that the events leading to this hyperphosphorylation are related to mitotic mechanisms. Hence, we have analyzed the physiological phosphorylation of endogenous tau protein in metabolically labeled human neuroblastoma cells and in Chinese hamster ovary cells stably transfected with tau. In nonsynchronized cultures the phosphorylation pattern was remarkably similar in both cell lines, suggesting a similar balance of kinases and phosphatases with respect to tau. Using phosphopeptide mapping and sequencing we identified 17 phosphorylation sites comprising 80–90% of the total phosphate incorporated. Most of these are in SP or TP motifs, except S214 and S262. Since phosphorylation of microtubule-associated proteins increases during mitosis, concomitant with increased microtubule dynamics, we analyzed cells mitotically arrested with nocodazole. This revealed that S214 is a prominent phosphorylation site in metaphase, but not in interphase. Phosphorylation of this residue strongly decreases the tau–microtubule interaction in vitro, suppresses microtubule assembly, and may be a key factor in the observed detachment of tau from microtubules during mitosis. Since S214 is also phosphorylated in Alzheimer’s disease tau, our results support the view that reactivation of the cell cycle machinery is involved in tau hyperphosphorylation.